A novel propylene glycol alginate gel based colorimetric tube for rapid detection of nitrite in pickled vegetables. (30th March 2022) - Zhang, Jing; Yang, Jianfei; Chen, Jing; Zhu, Yuanting; Hu, Kun; Ma, Qian; Zuo, Yong
Highlights: A simple and fast gel colorimetric tube for nitrite detection was developed. The colorimetric tube exhibited great selectivity and anti-interference ability. The method is helpful for real-time and on-site detection of nitrite in vegetables. Abstract: The detection of nitrite is of great significance because it is closely related to food safety. In this work, a rapid colorimetric method was developed for nitrite detection based on the reaction of propylene glycol alginate (PGA) gel interface. In the reaction of nitrite and 4-Aminoacetophenone, diazo compound formed, which could be further transformed to purplish red compound by reacting with N-(1-Naphthyl)ethylenediamine (NED). Nitrite exhibited a linear relationship with the grayscale of the gel interface in the range of 0.3–9 μg mL −1 with a detection limit of 0.3 μg mL −1 . The method was applied to detect nitrite in four types of pickled vegetables with recovery of 80.9–119.02% and relative standard deviation of 0.11–6.73%. Notably, the detection process can be accomplished within 5 min. The proposed colorimetric method exhibited advantages of simplicity, quickness and sensitivity, showing potential application prospects for the real-time and on-site detection of nitrite in pickled vegetables.